2013
DOI: 10.1111/jam.12178
|View full text |Cite
|
Sign up to set email alerts
|

Fungi and mycotoxins in silage: an overview

Abstract: Summary The present revision shows the early and current knowledge in the field of silage fungi and mycotoxins explaining the relevance of fungi and mycotoxins in silage. The problem does not end in animal disease or production losses as mycotoxins in feed can lead to the presence of their metabolic products in dairy products, which will be eventually affecting human health, mainly infants. Silage is green forage preserved by lactic fermentation under anaerobic conditions. This ecosystem maintains its quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
118
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(128 citation statements)
references
References 30 publications
2
118
0
7
Order By: Relevance
“…Little information is available with regard to the epiphytic fungal communities in silage, although the presence and growth of mycotoxigenic fungi has been extensively studied [52]. Barley and oat forages can be heavily colonized by mycotoxigenic fungi such as Fusarium which belongs to the Hypocreales [53].…”
Section: Discussionmentioning
confidence: 99%
“…Little information is available with regard to the epiphytic fungal communities in silage, although the presence and growth of mycotoxigenic fungi has been extensively studied [52]. Barley and oat forages can be heavily colonized by mycotoxigenic fungi such as Fusarium which belongs to the Hypocreales [53].…”
Section: Discussionmentioning
confidence: 99%
“…If this process does not occur in the proper conditions it could lead to the growth of yeasts that increase the pH followed by an increase in temperature. If the pH increases above the critical limits, the development of other microorganisms that spoil the silage such as Aspergillus species, one of the most common genera isolated in silage, can occur (Weissbach 1996;El-Shanawany et al 2005;Garon et al 2006;González Pereyra et al 2008;Alonso et al 2013). Aspergillosis is defined as the tissue damage caused by fungi of the genera Aspergillus (Vanden Bossche 1988).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Aspergillus fumigatus is a widely distributed saprophytic fungus that can be found in the soil or decaying organic matter where it performs an essential role in the carbon and nitrogen cycle. Previous studies have shown the prevalence of Aspergillus species in silage and finished feed for cattle in feedstuffs (González Pereyra et al 2008, 2011Pereyra et al 2008;Keller et al 2012;Alonso et al 2013).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Aspergillus fumigatus, the most common cause of invasive aspergillosis in immunocompromised individuals, is a common fungus found in contaminated animal feed (Alonso et al 2013). This fungus is able to produce tremorgenic mycotoxins and to induce neurological syndromes in farm workers who have manipulated mouldy feed (Gordon et al 1993).…”
Section: Introductionmentioning
confidence: 98%